The use of lyophilized plasma in a severe multi‐injury pig model. (10th January 2013) - Lee, Tim H.; Van, Philbert Y.; Spoerke, Nicholas J.; Hamilton, Gregory J.; Cho, S. David; Watson, Kate; Differding, Jerome; Schreiber, Martin A.
Abstract : Background: Shock and severe tissue injury lead to an endogenous coagulopathy mediated by activation of Protein C and hyperfibrinolysis known as acute traumatic coagulopathy. Together, hemodilution, acidosis, inflammation, and hypothermia result in a global trauma‐induced coagulopathy. Coagulopathy in trauma is associated with mortality. Early and effective hemostatic resuscitation is critical in restoring perfusion, correcting coagulopathy, and saving lives in exsanguinating trauma. Lyophilized plasma (LP) provides a logistically superior alternative to fresh frozen plasma (FFP). Study Design and Methods: Plasma was lyophilized following whole blood collection from anesthetized swine. A series of studies were performed using anesthetized swine subjected to a validated model of polytrauma and hemorrhagic shock including a Grade V liver injury. Animals were randomized to resuscitation using reconstituted LP fluids. Physiologic data and blood loss were measured. Coagulation status and inflammatory mediators were evaluated. Results: Full volume reconstituted LP (100%LP) retains on average 86% coagulation factor activity compared to fresh plasma and when used in 1:1 ratios with red blood cells demonstrated superior hemostatic efficacy compared to FFP. Hypertonic LP reconstituted using 50% of the original plasma volume (50%LP) had higher coagulation factor concentrations, was well tolerated in swine, and equally effective compared to 100%LP with respect to physiologic and hemostatic properties. Buffering with ascorbic acid resulted in significant reductions in serum levels of tumor necrosis factor alpha and interleukin‐6. Conclusion: By minimizing the volume of reconstituted LP and optimizing its anti‐inflammatory properties, an LP resuscitation fluid may be created to provide effective hemostatic resuscitation with superior logistical properties.